Cultural competency : perceptions of South African trained occupational therapists - Leendertz, Alethea Ethel (My University, 2013)
During occupational therapy training in South Africa, students are expected to consider cultural differences when working with patients. This study considered the training offered to students in terms of cultural diversity and the perceptions of 47 novice community service occupational therapists about their cultural competence as well as how these perceptions had changed after three years of clinical practice. Results indicate that all six participating universities offer training in cultural diversity although university respondents feel this is affected by time, students’ attitudes and their inability to reflect. Most newly qualified occupational therapists felt the training was adequate, although they reported difficulty in working with patients from other cultures in clinical practice. The perceived cultural competency level of the newly qualified respondents varied with some respondents still needing to develop awareness and knowledge and others already extending themselves in terms of cultural skill, encounters and cultural desire. Some used rules and knowledge to guide their intervention and language was seen as a major barrier to practicing culturally appropriate occupational therapy, Three years later three respondents, who could be considered competent occupational therapists, reported using reflection in practice enabled them to consider culture from their clients’ unique perspective. They felt personal experience, opportunities from classroom experiences, fieldwork exposure and professional development activities should be used to strive toward becoming culturally competent. The importance of having relevant resources available was highlighted. Recommendations for occupational therapy curriculum development in terms of cultural competence in South Africa are therefore suggested.
Keywords: Occupational Therapy; Cultural Diversity